ANATOMICAL PROPERTIES AND FIBER DIMENSION OF PRICKLY ACACIA (Acacia nilotica L.) FROM BALURAN NATIONAL PARK - Krisdianto, Krisdianto; Damayanti, Ratih (Secretariat of Forestry Research and Development Agency, 2007)
Acacia nilotica (L.) Willd. ex. Delile growing in Baluran National Park has dramatically altered the ecological balance of grasslands and thereby threatens the existence of local biodiversity. Prickly acacia is able to spread rapidly and remains uncontrollable. Baluran National Park authorization has been struggling to control this prickly acacia trees. One possible action that can be taken to encounter this problem is allowing wood based industries, and local people take advantages of this nilotica timber utilization. This paper studies the anatomical properties and fiber dimensions of nilotica timber and discusses the possible utilization of nilotica timber. This timber is characterized by dark brown heartwood which is clearly distinct from reddish brown color of sapwood. The denser cell wall shows attractively streaked in tangential surfaces. The length of wood fiber decreases from pith toward periphery portion. Longitudinally, higher stem has shorter fiber. Nilotica wood has second class quality of fiber, which means its fiber is moderately thick with narrow lumen diameter. Due to small log diameter and branches, the nilotica timber is not recommended for construction material. The timber is suitable for carved and turnery products. Nilotica timber is suitable for charcoal manufacture and fuel wood due to its high calorific value.